Building a Worship Demand Application with The Waterfall Method Using Flutter Framework at The Al-Muttaqin Mosque Suralaga, Indonesia - Ahmad Subki; Muhamad Masjun Efendi; Erfan Wahyudi (Yayasan Hisnul Muslim Lombok, 2024)
With the rapid development of modern technology such as smartphones, it has positive and negative impacts in this modern era. The positive impact is easy access to information. Meanwhile, the negative impact is misuse of the smartphone itself, such as opening websites that are not suitable for viewing, one of which is addiction to internet games which makes you lazy about studying. Apart from that, there is also a significant problem, namely travelers and children or teenagers at the Al-Muttaqin Mosque in Suralaga who seem to have quite difficulty carrying religious guidance in the form of a book. To overcome this, an Android-based prayer guidance application was created. It is hoped that this can provide understanding for children and teenagers at the Al-Muttaqin Mosque in Suralaga. As a result, this application was built using the Flutter Framework and the Waterfall method which consists of the user needs analysis stage, namely analyzing what needs and features are needed when creating the application. The design stage is the system design stage using System Flowcharts, UML (Use Case, Class and Activity) diagrams. The implementation stage is the stage of implementing the UI/UX design into a programming language using Visual Studio Code. The final testing stage is the stage of testing the functionality of the application using black box testing and using usability. The results of black box testing show that all menus were successfully executed and the results of usability testing using a Likert scale were 84.8%. This shows that in terms of utility the application built is in the